Young People's Information-seeking in School - A Breeding Ground for Digital Inequality? - Ulli Samuelsson (Universitetsforlaget, 2012)
This article describes and discusses the digital and information skills of Swedish youth in relation to educational goals and e-society participation, following pioneering research done by van Dijk, Buckingham, and Enochsson on this subject. By the findings from a questionnaire and interviews, a diversified picture of information skills and attitudes toward being a part of the e-society emerge - a picture that supports the idea that the school could contribute to the establishment of digital inequalities among the students. Keywords: Digital skills, information-seeking, digital inequality.